‘You need to research your subject so you know the subject well, and your users so you know what they need’. Teaching graphic design using information design principles. - Potter, Eden J. (InfoDesign, 2013)
Set against a background of graphic design’s <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: Arial; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">‘identity crisis’, this paper proposes that information design can provide an adaptable and relevant framework for teaching graphic design. With social, technological, environmental, and industrial changes providing a new context for design and how it operates in the world, an audience-focussed, problem-solving approach is validated as central to reimagining graphic design education. Through a case study example, the paper suggests that when graphic design students in a traditional craft-based design education programme are offered a human-centred approach to solving design problems—specifically information design problem solving and research methods—their own graphic design practice changes.